Towards fair health policies for migrants and ethnic minorities: the case-study of ETHEALTH in Belgium - Dauvrin Marie; Derluyn Ilse; Coune Isabelle; Verrept Hans; Lorant Vincent (BMC, 2012)
Abstract Background In Europe, progress in the development of health policies that address the needs of migrants and ethnic minorities has been slow. This is partly due to the absence of a strategic commitment by the health authorities. The Ministry of Public Health commissioned the ETHEALTH (EThnicity &HEALTH) group to formulate relevant recommendations to the public authorities with a view to reducing health inequalities among ethnic minorities. This paper describes the political process and the outcomes of the ETHEALTH expert group. Results After ten meetings, the ETHEALTH group came up with 46 recommendations, which were presented at a national press conference in December 2011. Target groups concerned by these recommendations covered both irregular migrants and migrants entitled to the national insurance coverage. Recommendations were supported by the need of combining universal approaches to health care with more specific approaches. The scope of the recommendations concerned health care as well as prevention, health promotion and access to health care. When analysing the content of the recommendations, some ETHEALTH recommendations were not fully measurable, and time-related; they were, however, quite specific and realistic within the Belgian context. The weak political commitment of an executive agency was identified as a major obstacle to the implementation of the recommendations. Conclusions The ETHEALTH group was an example of scientific advice on a global health issue. It also demonstrated the feasibility of coming up with a comprehensive strategy to decrease ethnic health inequalities, even in a political context where migration issues are sensitive. Two final lessons may be highlighted at the end of the first phase of the ETHEALTH project: firstly, the combination of scientific knowledge and practical expertise makes recommendations SMART; and, secondly, the low level of commitment on the part of policymakers might jeopardise the effective implementation of the recommendations.